Análise parasitológica do coentro (Coriandrum sativum L.) comercializado em feira livre no município de Apodi, estado do Rio Grande do Norte - Marinho, Sara Cilea Mendes Freire (Universidade Federal Rural do Semi-Árido, 2018)
Coriander (Coriandrum sativum), is a very consumed ingredient in Brazilian cuisine, due to its nutritive and spice value. When this occurs, the consumption of refrigerant can be transmitted by food, among which can be highlighted the parasitic diseases. This content is an important contamination for enteroparasites presented in specimen of the species of Coriandrum sativum L., commercialized in the free market of the city of Apodi, State of Rio Grande do Norte. In processing 250 ml of distilled water were added to 100 g of the samples followed by homogenization for 30 seconds with subsequent sieving of the obtained liquid and spontaneous sedimentation for 24 hours according to Hoffman (1987). The analyzes were applied in triplicate and the parasites were diagnosed in optical microscopes (10 and 40X). From the collections made during the period from February 2017 until January 2018, a total of 120 samples of coriander were analyzed. Regarding the results they had, 85% (102/120) of the samples were negative and 15% (18/120) positive. Of these, 85% (102/120) of the samples were negative and 15% (18/120) positive. Of these, 5.55% (1/18) contaminated with egg and 11.11% (2/18) larvae of the genus Toxocara sp; The larvae of the genus Strongyloides sp. Were the most common species of larvae of the genus Ancylostomum sp and 11.11% (2/18) eggs of the same genus and 66.66% (12/18). With the results obtained it was possible to diagnose the coriander marketed at the fair, with the degree of parasitic contamination with pathogenic potential over what is able to measure hygienic-sanitary during the manipulation of planting until the sale of coriander at the fair. in the case of the water is a high end food.
Monografia
Keywords: Contaminação alimentar; Hortaliças; Parasitos; Food contamination; Vegetables; Parasites; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA